2017
DOI: 10.1111/cdev.12858
|View full text |Cite
|
Sign up to set email alerts
|

Getting to No: Pragmatic and Semantic Factors in Two‐ and Three‐Year‐Olds' Understanding of Negation

Abstract: Although infants say "no" early, older children have difficulty understanding its truth-functional meaning. Two experiments investigate whether this difficulty stems from the infelicity of negative sentences out of the blue. In Experiment 1, given supportive discourse, 3-year-olds (N = 16) understood both affirmative and negative sentences. However, with sentence types randomized, 2-year-olds (N = 28) still failed. In Experiment 2, affirmative and negative sentences were blocked. Two-year-olds (N = 28) now suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…These findings suggest that negative sentences are processed in a fully incremental manner as long as they are used in an appropriate pragmatic context, supporting the view that negation is inherently contextual (e.g., Glenberg, Robertson, Jansen, & Johnson-Glenberg, 1999) and that negatives are not necessarily any more difficult to process than affirmatives (e.g., Johnson-Laird & Tridgell, 1972;Wason 1965). Developmental research has identified similar patterns in young children: for example, negative sentences are more readily understood and accepted by 3-and 4-year-olds when presented in a pragmatically supportive context (Nordmeyer & Frank, 2018), although 2-year-olds appear to have more fundamental difficulties with semantic processing of truth-functional negation (Reuter, Feiman, & Snedeker, 2018).…”
Section: /67mentioning
confidence: 99%
“…These findings suggest that negative sentences are processed in a fully incremental manner as long as they are used in an appropriate pragmatic context, supporting the view that negation is inherently contextual (e.g., Glenberg, Robertson, Jansen, & Johnson-Glenberg, 1999) and that negatives are not necessarily any more difficult to process than affirmatives (e.g., Johnson-Laird & Tridgell, 1972;Wason 1965). Developmental research has identified similar patterns in young children: for example, negative sentences are more readily understood and accepted by 3-and 4-year-olds when presented in a pragmatically supportive context (Nordmeyer & Frank, 2018), although 2-year-olds appear to have more fundamental difficulties with semantic processing of truth-functional negation (Reuter, Feiman, & Snedeker, 2018).…”
Section: /67mentioning
confidence: 99%
“…We tested children's interpretation of both known and unknown numbers using the "Don't Give-a-Number" task. Although it is unclear when English-speaking children begin to understand don't, recent work shows that they comprehend the words no, not, and didn't as markers of logical negation shortly after they turn two (Austin, Theakston, Lieven, & Tomasello, 2014;Feiman, Mody, Sanborn, & Carey, 2017;Reuter, Feiman, & Snedeker, 2018). Children at this age are typically non-knowers or 1-knowers, with many numbers still left to learn.…”
Section: Methodsmentioning
confidence: 99%
“…While previous studies have found that children as young as 2 years of age comprehend the logical meaning of words like no, not, and didn't (Austin, et al, 2014;Feiman, et al, 2017;Reuter, et al, 2018), these studies have focused on children's comprehension of negation in the service of exclusion inferences between one of two options. For example, given two options (e.g., a bucket and a truck), and told that a hidden ball is not in one of them, 2-year-olds search in the other.…”
Section: Negation and Entailment In Childhoodmentioning
confidence: 99%
“…Different conclusions were drawn from the eyetracking study described by Reuter et al (2018). Reuter et al (2018) investigated processing of “didn’t” by 2- and 3-year-old children.…”
Section: Introductionmentioning
confidence: 99%
“…Different conclusions were drawn from the eyetracking study described by Reuter et al (2018). Reuter et al (2018) investigated processing of “didn’t” by 2- and 3-year-old children. When Reuter et al provided children with both pragmatic (e.g., story contexts that created expectations for negation) and semantic (blocking of affirmative and negated trials) supports, even 2-year-olds showed above chance accuracy interpreting negation.…”
Section: Introductionmentioning
confidence: 99%